Can Plasma α-Synuclein Help Us to Differentiate Parkinson's Disease from Essential Tremor?. Issue 1 (28th May 2021) - Albillos, Silvia M.; Montero, Olimpio; Calvo, Sara; Solano, Berta; Trejo, José María; Cubo, Esther
Background: Studies have revealed controversial results regarding the diagnostic accuracy of plasma α-synuclein levels in patients with Parkinson's disease (PD). This study was aimed to analyze the diagnostic accuracy of plasma α-synuclein in PD versus healthy controls and patients with essential tremor (ET). Methods: In this cross-sectional study, we included de novo (n = 19) and advanced PD patients [OFF (n = 33), and On (n = 35) states], patients with ET (n = 19), and controls (n = 35). The total plasma α-synuclein levels were determined using an ELISA sandwich method. We performed adjusted multivariate regression analysis to estimate the association of α-synuclein levels with group conditions [controls, ET, and de novo, OFF and ON-PD]. We studied the diagnostic accuracy of plasma α-synuclein using the area under the curve (AUC). Results: The plasma α-synuclein levels were higher in controls compared to PD and ET (p < 0.0001), discriminating de novo PD from controls (AUC = 0.74, 95% CI 0.60–0.89), with a trend towards in advanced PD (OFF state) from ET (AUC = 0.69, 95% CI 0.53–0.84). Conclusions: This is the first study examining and comparing plasma α-synuclein levels in ET vs. PD and controls. Preliminary findings suggest that plasma α-synuclein levels might help to discriminate de novo and advanced PD from controls and ET.